Dynamically Stable Sets in Infinite Strategy Spaces. - Norman, T (Department of Economics (University of Oxford), 2005)
Evolutionary game theory has largely focused on finite games. Dynamic stability is harder to attain in infinite strategy spaces; Bomze (Monatshefte fÄur Mathematik 110, 1990, 189{206) and Oechssler and Riedel (Economic Theory 17, 2001, 141{162) provide conditions for the stability of rest points under the replicator dynamics. Here, conditions are given for the stability of sets of strategies under this process.